2016
DOI: 10.1093/humrep/dew148
|View full text |Cite
|
Sign up to set email alerts
|

RCT to evaluate the influence of adjuvant medical treatment of peritoneal endometriosis on the outcome of IVF

Abstract: 8 March 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…Our study showed no clear negative effect of the lower LH level in the control group. However, ultralong pituitary downregulation may suppress the ovarian response to Gn [26], and our results are consistent with this finding. The control group required a higher Gn dose and longer time for stimulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed no clear negative effect of the lower LH level in the control group. However, ultralong pituitary downregulation may suppress the ovarian response to Gn [26], and our results are consistent with this finding. The control group required a higher Gn dose and longer time for stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…Conflicting results have been reported regarding oocyte quality between patients with EMs and controls [25]. A randomized controlled trial showed that 3-month GnRH agonist treatment for peritoneal EMs prior to IVF did not produce a better outcome, such as a greater number of MII oocytes, compared with a longer protocol [26]. Van der Houwen found that ultralong pituitary downregulation can achieve a limited favorable effect in ongoing pregnancy in women who had experienced severe EMs during fresh cycles [27].…”
Section: Discussionmentioning
confidence: 99%
“…Predictably, higher doses of FSH and a longer stimulation were also required for ovarian stimulation in the group receiving GnRH agonist pre-treatment. However, patients included were women not affected by ovarian endometriosis and surgically treated for peritoneal endometriosis, who were either assigned to immediate IVF after surgery or to post-surgical 3-month GnRH agonist treatment and subsequent IVF [84]. Hence, no information can be obtained about the benefits of GnRH agonist in the presence of ovarian endometriomas or in patients who have not undergone surgical treatment for endometriosis.…”
Section: Potential Impact On Clinical Practicementioning
confidence: 99%
“…PR are also enhanced if GnRH agonists are administered prior to IVF. Postoperative medical treatment does not seem to incite a rise in PR, in women aiming at spontaneous conception, while they also add an unwanted time delay ( 30 , 81 ). Opøien et al ( 82 ), have underlined the important role of surgery in eradicating macroscopic lesions.…”
Section: Endometriosis-associated Infertilitymentioning
confidence: 99%